Evaluation of the Mitochondrial Respiratory Chain and Oxidative Phosphorylation System using Polarography and Spectrophotometric Enzyme Assays - Barrientos, Antoni (2009)
The oxidative phosphorylation (OXPHOS) system consists of five multimeric complexes embedded in the mitochondrial inner membrane. They work in concert to drive the aerobic synthesis of ATP. Mitochondrial and nuclear DNA mutations affecting the accumulation and function of these enzymes are the most common cause of mitochondrial diseases and have also been associated with neurodegeneration and aging. For this reason, several approaches for the assessment of the OXPHOS system enzymes have been developed. Based on the methods described elsewhere, we present here assays for a biochemical characterization of the OXPHOS system in cells and mitochondria isolated from cultured cells or tissues.